Experimental warming advances phenology of groundlayer plants at the boreal‐temperate forest ecotone. Issue 5 (6th June 2018) - Rice, Karen E.; Montgomery, Rebecca A.; Stefanski, Artur; Rich, Roy L.; Reich, Peter B.
Abstract : Premise of the Study: Changes to plant phenology have been linked to warmer temperatures caused by climate change. Despite the importance of the groundlayer to community and forest dynamics, few warming experiments have focused on herbaceous plant and shrub phenology. Methods: Using a field study in Minnesota, United States, we investigated phenological responses of 16 species to warming over five growing seasons (2009–2013) at two sites, under two canopy covers, and in three levels of simultaneous above‐ and belowground warming: ambient temperature, ambient +1.7°C and ambient +3.4°C. We tested whether warming led to earlier phenology throughout the growing season and whether responses varied among species and years and depended on canopy cover. Key Results: Warming extended the growing season between 11–30 days, primarily through earlier leaf unfolding. Leaf senescence was delayed for about half of the species. Warming advanced flowering across species, especially those flowering in August, with modest impacts on fruit maturation for two species. Importantly, warming caused more than half of the species to either converge or diverge phenologically in relation to each other, suggesting that future warmed climate conditions will alter phenological relationships of the groundlayer. Warm springs elicited a stronger advance of leaf unfolding compared to cool spring years. Several species advanced leaf unfolding (in response to warming) more in the closed canopy compared to the open. Conclusions: Climate warming will extend the growing season of groundlayer species in the boreal‐temperate forest ecotone and alter the synchrony of their phenology.